Malay minorities in The Tenasserim coast - Mar, Ma Tin Cho; Trang, Pham Huong (UI Scholars Hub, 2020)
This paper discusses the Malay Minorities of the Malay Minorities in the Tenasserim Coast. And Tanintharyi Division is an administrative region of Myanmar at present. When we look closely at some of the interesting historical facts, we see that this region is “Tanao Si” in Thai, or Tanah Sari in Malay. This region belonged to Tanah Melayu, or Malay Peninsula, which was part of the Sultanate of Kedah. It was occupied first by the Ayutthaya Kingdom and later by Burma. Moken people of the Austronesian-speaking tribes who live on the coast and on the islands of the Andaman Sea up through the Mergui Archipelago of Myanmar have rationally attracted the attention of researchers. The group includes the Mokens themselves, the Moklen (Moklem), the Orang Sireh (Betel-leaf people) and the Orang Lanta. The Orang Lanta are a hybridized group formed when the people of Malay settled in the Lanta Islands, where the proto-Malay Orang Sireh had lived. The Burmese call the Mokens